A Practical Verification Methodology for Concurrent Programs - Moskal, Michal; Schulte, Wolfram; Cohen, Ernie; Tobies, Stephan (Microsoft, 2009)
We describe a methodology for reasoning about realistic concurrent programs. Our methodology allows two-state invariants that span multiple objects without sacrificing thread- or data-modularity, as well as the derived construction of first-class objects that capture knowledge about the system state. The methodology has been implemented in an automatic sound verifier for concurrent C programs being used to verify the code of the Microsoft Hypervisor, the virtualization kernel of Hyper-V.